KONVERSI BIOWASTE MENJADI BIOENERGI DAN BIOPRODUK: TINJAUAN DALAM CIRCULAR BIO ECONOMY - Siti Fauziah; Ervan hasan Harun; Jumiati Ilham (Program Vokasi-Universitas Negeri Gorontalo, 2026)
The transition toward low-carbon energy systems has repositioned biowaste as a strategic resource within the circular bioeconomy, offering potential to enhance resource efficiency, reduce greenhouse gas emissions, and generate value-added bioproducts. This review aims to analyze the relationship between biowaste characteristics and the selection of conversion pathways, evaluate recent advances in conversion technologies, and propose strategies for developing biorefineries that are technically, environmentally, and economically feasible. The study employs a systematic literature review approach, covering foundational and recent studies on pretreatment optimization, biological and thermochemical processes, and the integration of life cycle assessment (LCA) and techno-economic analysis (TEA). The synthesis reveals that no single technology is universally optimal for all types of biowaste; conversion efficiency depends on the alignment between feedstock composition, pretreatment methods, process configuration, and desired end-products. Anaerobic digestion remains the most suitable option for wet organic waste, while thermochemical processes such as pyrolysis and gasification are more appropriate for lignocellulosic biomass. Additionally, emerging approaches involving microalgae, nanotechnology, and machine learning contribute to improving system efficiency and product selectivity. In conclusion, the development of sustainable circular biorefineries requires feedstock standardization, data-driven process design, and the integration of LCA and TEA to support large-scale industrial implementation.